Rotator cuff repair just in local anesthesia is possible - M. Tinazzi; B. Rosato; M. Barca (Verduci Editore, 2023)
Objective: Rotator cuff repair consists of surgical tendon re-fix to the bone. Once the lesion has been identified, loco-regional anesthesia and general anesthesia are the anesthesiologic techniques preferentially used in the intervention for the resolution of the injury, but their use involves several side effects, such as hemidiaphragmatic paralysis, laryngeal nerve block, and pneumothorax. In literature, only one case report presents an arthroscopic repair of massive rotator cuff tears performed under local anesthesia and sedation: in this case, local anesthesia was preferred because of the failure of the locoregional block. Case presentation: In our work, we performed a mini-open rotator cuff repair on a 56-year-old woman with the use of simple local anesthesia, which allowed us to obtain a satisfactory result bypassing side effects deriving from other anesthetic techniques usually used. The patient recovered optimal abduction and good internal rotation of the limb, with a significant reduction in pain mobility. Conclusions: The prospect of performing surgical repair of the rotator cuff under local anesthesia is very interesting, allowing to avoid problems that can occur with general anesthesia administration or regional interscalene block.